Developing Educational Mobile Games to Train the Sensory Abilities of Preschool Children - Khairul, Khairul (Proceedings of The International Conference on Computer Science, Engineering, Social Science, and Multi-Disciplinary Studies, 2025)
This study aims to develop an educational mobile game that can train the sensory abilities of early childhood (PAUD). The game developed carries the concept of puzzles and guessing pictures specifically designed to improve children's visual sensory abilities, fine motor skills, and visual perception. In developing this game, a Research and Development (R&D) approach was used with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The trial was conducted on groups of PAUD children at several educational institutions in Medan, with direct observation of children's sensory development while using the game. The results showed that this mobile game was effective in improving children's sensory abilities, with positive feedback from children and teachers regarding the ease of use and the level of children's involvement during the game. This game can be used as an alternative learning medium that is fun and educational for early childhood.